Peran Public Relations Dalam Membentuk Persepsi Positif Terhadap Tiktok Shop - Gilang Wasis Danuarta; Tria Patrianti; Rochman Rayhan Maulana; Muhammad Farhan Nugraha (Lembaga Pengembangan Kinerja Dosen, 2024)
This research investigates the role of Public Relations (PR) in forming positive perceptions of TikTok Shop as an increasingly dominant e-commerce platform. This research involves analysis of PR communication strategies, image management, and interactions with stakeholders designed to create positive perceptions among consumers. Qualitative research methods were used to deepen understanding of how PR contributes to the formation of a positive image and relationship at TikTok Shop. The findings of this research highlight the importance of a proactive approach in responding to issues that can influence consumer perceptions of TikTok Shop.